PERANAN IBADAH KONTEKSTUAL BAGI PERTUMBUHAN ROHANI REMAJA DI GEREJA KRISTEN JAWA BATURETNO - THERESIA INSANI GUSTI; JUSTIN NIAGA SIMAN JUNTAK (CENDEKIA: Jurnal Ilmu Pengetahuan, 2023)
Every Christian in order to live the work of God's grace is generally expressed by the form of worship. In addition to the work of worship can be done with other things like praying, praising and otherwise, but the essence of this appeal is not only formality but to establish intimate relationship with the transcendent in a theological reflection. The church has a role to provide spiritual service to build and improve someone's religiusity, and every church certainly has a difference in the way in particular in theology of so that the model of worship between one church with another church has a difference with each reflection charge. One of the "consumers" in the worship is the teenager, they are with all sorts of background even motivation in worship will certainly assess a martyrity. They will wake up if the worship is in accordance with their expectations, therefore to accommodate their expectations then church critic thinking to provide non-monotonous services, full of VALUE and contextual. Through this writing the author wants to see the teenage and their spiritual growth through the role of the church in particular in a contextual worship. ABSTRAKSetiap umat kristen dalam rangka untuk menghayati karya anugrah Allah umumnya diekspresikan dengan wujud ibadah. Selain penghayatan ibadah dapat dilakukan dengan hal lain seperti berdoa, memuji dan lainya, namun esensi dari penghayatan ini bukan hanya semata formalitas melainkan menjalin relasi intim dengan sang transenden dalam sebuah refleksi teologis. Gereja memiliki peranan untuk memberikan pelayanan spiritual untuk membangun dan meningkatkan religiusitas seseorang, dan setiap gereja tentu memiliki perbedaan cara khususnya dalam penghayatan teologi sehingga model peribadahan antara satu gereja dengan gereja yang lain memiliki perbedaan dengan muatan refleksi masing-masing. Salah satu “konsumen” dalam peribadahan adalah jemaat remaja, mereka dengan segala macam latar belakang bahkan motivasi dalam beribadah tentu akan menilai sebuah peribadahan. Mereka akan terbangun jika peribadahan sesuai dengan harapan setiap mereka, oleh sebab itu untuk mengakomodir harapan mereka lantas gereja berfikir kritis untuk memberikan pelayanan yang tidak monoton, penuh dengan value dan kontekstual. Melalui tulisan ini penulis ingin melihat penghayatan remaja dan pertumbuhan rohani mereka melalui peranan gereja khususnya dalam sebuah peribadahan kontekstual.